Enhanced Detection of Major Pathogens and Toxins in Poultry and Livestock With Zoonotic Risks Using Nanomaterials-Based Diagnostics - Manhas, Priya K.; Quintela, Irwin A.; Wu, Vivian C. H. (Frontiers in Veterinary Science, 2021)
Nanotechnology has gained prominence over the recent years in multiple research and application fields, including infectious diseases in healthcare, agriculture, and veterinary science. It remains an attractive and viable option for preventing, diagnosing, and treating diseases in animals and humans. The apparent efficiency of nanomaterials is due to their unique physicochemical properties and biocompatibility. With the persistence of pathogens and toxins in the poultry and livestock industries, rapid diagnostic tools are of utmost importance. Though there are many promising nanomaterials-based diagnostic tests specific to animal disease-causing agents, many have not achieved balanced sensitivity, specificity, reproducibility, and cost-effectiveness. This mini-review explores several types of nanomaterials, which provided enhancement on the sensitivity and specificity of recently reported diagnostic tools related to animal diseases. Recommendations are also provided to facilitate more targeted animal populations into the development of future diagnostic tools specifically for emerging and re-emerging animal diseases posing zoonotic risks.